Empowering Women’s Economic Through Entrepreneurship Training in the Coastal Community of Karang Serang Village, Sukadiri District, Tangerang Regency - Ahmad Jarkasih; Riza Dzul Fahmi Aly (International Journal of Management and Business, 2025)
This research and community activity is conducted in Karang Serang Village, Sukadiri District, Tangerang Regency, and aims to enhance the economic capacity of women through entrepreneurship training and seminars. Women in coastal areas play an important role in supporting the family economy, but still face various limitations, such as a lack of knowledge about entrepreneurship, limited access to training, and suboptimal use of technology for marketing. This activity is designed to provide basic education on entrepreneurship, including an introduction to micro business concepts, small business management strategies, and the use of digital media as a means for promotion and sales. The seminar was held face-to-face using a participatory method, involving discussions, case studies, and question-and-answer sessions. The participants comprised 50 women representing coastal community groups. The topics covered included motivation for entrepreneurship, business planning, simple financial recording, and digital marketing techniques through social media. The results of the activity indicate a significant increase in participants’ understanding of entrepreneurship concepts, an increase in self-confidence, and a growing motivation to start independent businesses. Some participants have even begun drafting business plans and developing products based on local potential, such as processed seafood and handicrafts. This activity demonstrates that the seminar approach is not only effective as a means of knowledge transfer, but also capable of fostering entrepreneurial spirit among women in coastal areas.